Total (Transthoracic and Transabdominal) Robotic Radical Three-Stage Esophagectomy—Initial Indian Experience - Somashekhar, S. P. (Indian J Surg, 2016)
This study aims to evaluate the safety and technical feasibility of total robot-assisted three-stage esophagectomy. From July 2011 to June 2014, 35 histologically proven resectable carcinoma esophagus patients underwent robot-assisted transthoracic and transperitoneal three-stage esophagectomy. In the initial ten cases, total docking time, thoracic docking time, total operative time, thoracic-phase operative time, and blood loss were 67.9 ± 13.24, 32.2 ± 9.74, 429.2 ± 57.65, and 96.6 ± 20.33 min and 433.20 ± 48.72 ml, respectively. In the subsequent 25 cases, all parameters decreased significantly (33.20 ± 4.16, 13.76 ± 3.43, 321.13 ± 13.75, and 57.04 ± 9.15 min and 256.32 ± 17.52 ml, respectively). Median numbers of lymph node dissected were 32. One case was converted to open method, and there was no in-hospital or 30-day mortality. Two cases required ventilator support for 1 day, with ICU stay for 1 day in 15 patients and 2 days in five patients. Two patients had major complications. Median hospital stay was 8 days. All had microscopic negative resection margins. Robot-assisted three-stage esophagectomy has the benefits of minimally invasive surgery and immediate oncological outcomes are comparable to conventional open surgery. Therefore, it is a safe and feasible technique for the treatment of esophageal cancer in selected patients.